Stable isotope data from the Ferrigno ice core (F10), Bryan Coast, West Antarctica - Thomas, Elizabeth (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2016)
This dataset provides a 308 year (1702-2009) deuterium isotope record from the Ferrigno 2010 (F10) ice core. The core was drilled on the Bryan Coast in Ellsworth Land, West Antarctica, during the austral summer 2010/11. The record was measured using a Los Gatos Liquid Water Isotope Analyser at 5cm resolution, corresponding to ~14 samples per year, with annual averages calculated for January-December.